Chapter 5.36 The Profession of Research Management and Administration in Norway - Nichole Elgueta Silva; Hege Nedberg (Emerald Publishing Limited, 2023)
This chapter focuses on the Norwegian research system and the Norwegian Research Management and Administration (RMA) community. The first section presents the overall Norwegian system of research and innovation, and the most important actors. In the second section of the chapter, our attention turns to the Norwegian RMA community, which is described through available data. We will look further into the evolution of the profession in Norway, who takes part in the current RMA community and lastly give an insight into what we know about Norwegian RMAs. Where do RMAs work, what is their background, what are their tasks and skills, and where is the development of Norwegian RMAs headed?
10.1108/978-1-80382-701-820231070; 10.1108/978-1-80382-701-820231070; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262